Investigating the Prevalence of PK Island in Enterobacteriacea - Nasser, Noor Ismeal; Alzubaidy, Fatima Hamza; Al-Saadi, Taif; Hashym, Qassim M.; Najem, Sura Abdul-Aziz (Medical Science Journal for Advance Research, 2026)
The Enterobacteriaceae family has a pathogenicity island that leads to increase in pathogenicity. Colibactin is a genotoxin that induces DNA double-strand breaks that may lead to carcinogenesis and is produced by Escherichia coli strains harboring the pks island. During study the detection of colibactin occurs by molecular method (polymerase chain reaction) followed by bacterial identification and DNA extraction. The result of study shows the bacterial E.coil is the most bacterial isolate found in enterobacteriacea sample used in study followed by Klebsiella contain the four genes that expressing of colibactin including (ClbA, ClbB, ClbQ and ClbN) representing the PK island.